Burden of non-communicable diseases from infectious causes in 2017: a modelling study. Issue 12 (December 2020) - Coates, Matthew M; Kintu, Alexander; Gupta, Neil; Wroe, Emily B; Adler, Alma J; Kwan, Gene F; Park, Paul H; Rajbhandari, Ruma; Byrne, Anthony L; Casey, Daniel C; Bukhman, Gene
Summary: Background: Non-communicable diseases (NCDs) cause a large burden of disease globally. Some infectious diseases cause an increased risk of developing specific NCDs. Although the NCD burden from some infectious causes has been quantified, in this study, we aimed to more comprehensively quantify the global burden of NCDs from infectious causes. Methods: In this modelling study, we identified NCDs with established infectious risk factors and infectious diseases with long-term non-communicable sequelae, and did narrative reviews between April 11, 2018, and June 10, 2020, to obtain relative risks (RRs) or population attributable fractions (PAFs) from studies quantifying the contribution of infectious causes to NCDs. To determine infection-attributable burden for the year 2017, we applied estimates of PAFs to estimates of disease burden from the Global Burden of Disease Study (GBD) 2017 for pairs of infectious causes and NCDs, or used estimates of attributable burden directly from GBD 2017. Morbidity and mortality burden from these conditions was summarised with age-standardised rates of disability-adjusted life-years (DALYs), for geographical regions as defined by the GBD. Estimates of NCD burden attributable to infectious causes were compared with attributable burden for the groups of risk factors with the highest PAFs from GBD 2017. Findings: Globally, we quantified 130 million DALYs from NCDs attributable to infection, comprising 8·4% of all NCD DALYs. The infection–NCD pairs with the largest burden were gastric cancer due to H pylori (14·6 million DALYs), cirrhosis and other chronic liver diseases due to hepatitis B virus (12·2 million) and hepatitis C virus (10·4 million), liver cancer due to hepatitis B virus (9·4 million), rheumatic heart disease due to streptococcal infection (9·4 million), and cervical cancer due to HPV (8·0 million). Age-standardised rates of infection-attributable NCD burden were highest in Oceania (3564 DALYs per 100 000 of the population) and central sub-Saharan Africa (2988 DALYs per 100 000) followed by the other sub-Saharan African regions, and lowest in Australia and New Zealand (803 DALYs per 100 000) followed by other high-income regions. In sub-Saharan Africa, the proportion of crude NCD burden attributable to infectious causes was 11·7%, which was higher than the proportion of burden attributable to each of several common risk factors of NCDs (tobacco, alcohol use, high systolic blood pressure, dietary risks, high fasting plasma glucose, air pollution, and high LDL cholesterol). In other broad regions, infectious causes ranked between fifth and eighth in terms of crude attributable proportions among the nine risks compared. The age-standardised attributable proportion for infectious risks remained highest in sub-Saharan Africa of the broad regions, but age-standardisation caused infectious risks to fall below dietary risks, high systolic blood pressure, and fasting plasma glucose in ranked attributable proportions within the region. Interpretation: Infectious conditions cause substantial NCD burden with clear regional variation, and estimates of this burden are likely to increase as evidence that can be used for quantification expands. To comprehensively avert NCD burden, particularly in low-income and middle-income countries, the availability, coverage, and quality of cost-effective interventions for key infectious conditions need to be strengthened. Efforts to promote universal health coverage must address infectious risks leading to NCDs, particularly in populations with high rates of these infectious conditions, to reduce existing regional disparities in rates of NCD burden. Funding: Leona M and Harry B Helmsley Charitable Trust.